Passivity and output feedback passification of switched continuous-time systems with a dwell time constraint. (August 2015) - Zhong, Guang-Xin; Yang, Guang-Hong
Abstract : Highlights: We investigate the passivity and output feedback passification of switched systems. A switching strategy which obeys a dwell time constraint is provided. This avoids too frequent switching. Dynamic output feedback controllers are designed to guarantee the passivity of the closed-loop system under the proposed switching strategy. Abstract: This paper is concerned with the passivity analysis and output feedback passification for a class of switched continuous-time systems. A switching law and control units are designed to guarantee the passivity of closed-loop switched systems. Different from the exist results in state-dependent switching framework, we construct a novel switching law such that the switched system obeys a minimal dwell time between any two consecutive switchings. This avoids the possible arbitrarily fast switching caused by state-dependent switching law. Moreover, the switching law uses only the lower bound of the dwell time and partial measurable states of the closed-loop system, which is applicable in output feedback framework. Using multiple discretized storage functions, the controllers working on different time intervals are obtained, which ensure the closed-loop system is passive under the switching law. Finally, two examples are provided to illustrate the effectiveness of the developed results.